The tango between pka and camkii signaling in cardiac pacemaker cells - Yaniv, Yael (2016)
The sinoatrial node is the primary pacemaker that controls the heart rate under normal conditions. Although the heart rate was originally measured thousands of years ago, the mechanisms that control the spontaneous beating of the sinoatrial node (SAN) are still under debate. In the last century, SAN function was mostly investigated by electrophysiological tools. Therefore, not surprisingly, the major mechanisms that control SAN function were thought to be related only to membranal ionic modulations. Recent biophysical, biochemical and imaging techniques have shed new light on the role of intrinsic pacemaker mechanisms on SAN function. Specifically, the role of post-translational modification signaling on SAN function has been explored using numerical and experimental tools. We describe here the major breakthroughs related to these signaling mechanisms in SAN cells. We conclude that the recent findings are only the tip of the iceberg in the fascinating world of downstream post-translational modification signaling, and we point out future research directions that may increase our knowledge of pacemaker function.